The Simple Aphasia Stress Scale - Laures-Gore, Jacqueline; Rice, Kenneth G. (Journal of speech, language, and hearing research, 2019)
Purpose: Clinically accessible and concise measures of acute stress in adults with aphasia are lacking. The current article evaluated some psychometric features of a single-item self-report measure of acute stress in adults with aphasia, the Simple Aphasia Stress Scale. Method: Three archival data sets utilizing varying iterations of a stress scale developed for studies of stress in adults with aphasia were included in the present analysis. Results: The single-item stress scale had good levels of absolute and relative stability. Scores were generally unaffected by aphasia severity, age, or sex. The scale was strongly correlated with emotional arousal. Conclusion: The single-item scale performed reasonably well across different studies and psychometric indicators. A 7-point rather than a 5-point response version of the scale was recommended as a clinically accessible and concise measure of acute stress in adults with aphasia. Future research should examine whether the tendency for adults with aphasia to use a restricted range of lower stress responses was due to underreporting, not perceiving acute stress, or some other factor. The high correlation between stress and arousal in women suggests that there needs to be further investigation of discriminant validity. Future work should also expand the scope of variables to evaluate further evidence of convergent and criterion-related validity.